二氧化碳和阳光紫外辐射对坛紫菜丝状体光合生理特性的影响 - 杨雨玲; 李伟; 陈伟洲; 徐军田 (2013)
为了探索大型海藻生活史丝状体阶段对于海洋酸化与紫外辐射的响应,实验选取经济海藻坛紫菜的自由丝状体作为实验材料。实验设置两个CO2浓度,正常CO2浓度(390 PPMV)和高CO2浓度(1 000 PPMV);3种辐射处理,PAr处理(仅接受可见光)、PA处理(滤除uV-b)、PAb处理(全波长辐射)。研究结果表明,高CO2显著提高了坛紫菜自由丝状体的生长速率,但高CO2处理下坛紫菜自由丝状体中藻红蛋白、藻蓝蛋白、叶绿素A、类胡萝卜素及紫外吸收物质uVACS分别降低了7.3%、9.3%、19.8%、16.5%和18.7%。高CO2处理的坛紫菜自由丝状体最大光化学效率fV/fM,光能利用效率(α)及最大相对电子传递速率(rETrMAX)都显著高于正常CO2处理。太阳模拟器下处理的坛紫菜自由丝状体,PAr与PA处理下的抑制率,正常CO2与高CO2处理间无显著差异,然而在PAb处理下,高CO2处理的抑制率要高于正常CO2处理,这可能与其体内紫外吸收物质含量下降有关。PAr处理下的抑制率,无论是在正常CO2还是在高CO2处理下,都显著低于PA及PAb处理,而PA与PAb之间无显著差异。在未来海洋持续酸化的背景下,uV辐射的增加将会影响到坛紫菜自由丝状体的光合生理及生长。 To study the effects of ocean acidification and UV radiation on early life cycle stage of macroalgae,we selected the conchocelis of economic algae Pyropia haitanensis as our material.Two CO2 levels(ambient CO2,390 ppmv and high CO2,1 000 ppmv)and three irradianceswere set in the study.Results showed that high CO2 significantly enhanced the relative growth rate of conchocelis of P.haitanensis,but the contents of phycoerythrin,phycocyanin,chlorophyll a,carotenoid and UVACs were significantly reduced by 7.3%,9.3%,19.8%,16.5% and 18.7% under high CO2 condition,respectively.Maximum photochemical efficiency(Fv/Fm),light using efficiency(α)and maximum relative electron transport rate(rETRmax)were all significantly increased under high CO2 condition.When exposed to different light treatments,inhibition induced by PAR and PA had no significant differences between the thalli grown at high and ambient CO2.However,significant inhibition under PAB was found in the thalli grown at high CO2,which was closely related to the low concentration of UVACs in the thalli of conchocelis of P.haitanensis.Inhibition induced by PAR were all lower than PA and PAB in both high and ambient CO2 treatments,however,no difference was found between PA and PAB treatments.In future ocean,increased UVR would have great effects on photosynthesis and growth of P.haitanensis,especially under the background of ocean acidification. 国家自然科学基金项目(41106093); 广东省科技计划项目(2010B060200010;2010B020201015); 广东省汕头市科技计划项目(2010-126;2011-161)